Impact of non-pharmaceutical interventions on SARS-CoV-2 outbreaks in English care homes: a modelling study - Rosello, A; Barnard, RC; Smith, DRM; Evans, S; Grimm, F; Davies, NG; Deeny, SR; Knight, GM; Edmunds, WJ (BioMed Central, 2022)
Background COVID-19 outbreaks still occur in English care homes despite the interventions in place.